Doe Productivity Index And Sperm Quality Of Senduro Goats - Agus Budiarto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2018)
The purpose of this research was to examine the quality of Senduro buck and evaluate of Senduro goat doe Productivity Index doe. The first material used in this research was 155 of doe and 284 kid of Senduro goats. The method used in this research is a case study. Primary data was taken on the terms of a direct observation questionnaire was used as a tool concerning reproduction and weighing in body weight of kids of Senduro goat. The variables measured were litter size, kidding interval, mortality, and weaning weight. The second material used data Senduro male goat sperm 2 years old, were frozen. Frozen semen produced by adding glycerol at various levels. The results of the research in the Senduro subdistrict showed that the average litter size is 1.83 ± 0.69 tail, average kidding interval is 281.87±37.66 days, the percentage of mortality is 4.93% of kid, the average weaning weight is 22.14±4.19 and Senduro goat doe productivity index is 50.87±23. 43 kg/year. The addition of glycerol was significantly different (p< 0.01) on the percentage of post-thawing motility, viability, abnormalities and a total number of motile spermatozoa. The conclusion of this research is the Senduro goat doe productivity index in the Senduro subdistrict amounted to 50.87±23,43kg/year. Value Senduro goats doe productivity index can reach a maximum when the number of litter size high, kidding interval short, mortality percentage of kid pre-weaning of Senduro goat low and weaning weight high. Selection of male goats Senduro, sheep based on body size and the size of their testes according to standard ISO. The process of sperm production in the form of frozen semen meets the quality standards ISO (PTM 40 percent).